Tax Treatment of Commuter Cost - Vidar Christiansen; Odd E. Nygård (Center for Economic Studies and ifo Institute (CESifo), 2024)
The paper discusses the tax treatment of commuting where wages and housing cost vary across locations. An income tax distorts the locational choices of agents, who dislike commuting and have preferences for place of residence Wages, housing cost and commuting cost determine how subsidising or taxing commuting affects behaviour and social efficiency. A subsidy encourages commuting and induces agents to choose a more favourable living place. The analysis clarifies the circumstances in which the subsidy alleviates or exacerbates the tax distortions, also where housing is tax favoured, as is often the case. The distributional impact depends on the effects of wages on commuting. An empirical illustration based on Norwegian data shows how one can infer efficiency effects of responses to subsidies on commuting.
Keywords: H21; H24; 330; income tax; commuting; commuter cost; subsidies on commuting; place of residence